STUDI EKSPLORASI TENTANG KOMPETENSI TENAGA PENDIDIK FAKULTAS EKONOMI UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Wahyu Nur Indah Sari (MNJ 16 UMY 256, 2016)
This research is motivated by the condition of Indonesian people who will come Humans are required to have quality human resources qualified and competent in the face of global competition. Quality All that can be generated through the organization of quality education and qualified. To support the implementation of quality education in this case one of the elements that have an important role that educators have 4 levels of competence under the Act. As for the issue of this research is "Is there a difference between pedagogical competence, professional competence, personal competence and social competence viewed from age, gender, academic position, level of education and educators working lives?". In this study, data were collected through questionnaires to teachers of the Faculty of Economics, University of Muhammadiyah Yogyakarta. The 36 questionnaires returned questionnaires. Then do the Validity and Reliabitas of the data obtained. The analysis tool uses analysis tools in the form of Independent sample t-test to test 2 samples (education level and gender) and One Way ANOVA to test more than 2 samples (age, academic position, and years of service). Obtain analysis results that were no differences between the level of pedagogical competence, professional competence, personal competence and social competence educators viewed from age, gender, academic position, level of education and educators working period. Keywords : Competence